Edukasi Pengawasan, Kepemimpinan dan Kompensasi terhadap Disiplin Kerja Karyawan Pada Masyarakat di Kecamatan Medan Denai - Juniarti; Putri Pradini (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
The purpose of this community service is to increase understanding of supervision, leadership and compensation on employee work discipline in the community in Medan Denai sub-district. The specific target in this community service is that the people of Medan Denai sub-district know what supervision, leadership and compensation are that affect work discipline. The materials presented in this community service are: what is supervision, leadership, and compensation. The relationship will affect employee work discipline in Medan Denai sub-district so that the community gets a solution in improving supervision, leadership, and compensation. From this community service, the results show that the Medan Denai sub-district community has known and understood the importance of supervision, leadership, and compensation to employees so that the community is able to improve work discipline and better work performance.